Utilization of Palm Oil Wastewater as Raw Material Alternative for Transformer Insulation Oil - Dwi Sinthya Kusumawardani; Tuti Emilia Agustina; M. Abu Bakar Siddik (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2020)
Insulator oil is one of important parts in transformer, in a form of a liquid, functioned as insulating and cooling media. The insulator oil made of mineral oils used in transformer potentially causes environmental problems, especially when an explosion occur inside the transformer which may cause oil spill or water contamination. Here, we study the used of Palm Oil Mill Effluent (POME) as the raw material for insulation oil. In this work, POME was extracted, distilled, measured the acid value followed by esterification and transesterification processes to obtain the insulation oil. The viscosity, flash point, acid value, and breakdown voltage of the insulation oil was measured. In the esterification process, HCl catalyst was added with a ratio of 1.5% to degrade the acid value of the oil, while in the transesterification process, NaOH or KOH catalysts were added with a ratio of 1.5 and 3%. The result for KOH catalyst is as follows, viscosity were 2.09 and 2.32 cSt, the flash point were 166 and 170oC, and the acid value were 0.5 mg KOH/g after the addition of 1.5 and 3% catalyst respectively, while the breakdown voltage was 55 kV after the addition of 1.5% KOH catalyst. NaOH catalyst shows result: viscosity were 5.34 and 5.02 cSt, the flash point were 178 and 183oC, and the acid value were 0.5 mg KOH/g after the addition of 1.5 and 3% catalyst, respectively, while the breakdown voltage was 46 kV after the addition of 1.5% KOH catalyst.